Examination of Prospective Science Teachers’ Levels of Designing Project Directed to National Support Programs: A Profile of Turkey - Gülşah Sezen Vekli (Universitas Pendidikan Indonesia, 2020)
This study aims to determine prospective science teachers’ levels of designing projects about The Scientific and Technological Research Council of Turkey, written in the abbreviation TUBITAK’s 2209-A “Support for University Students’ Research Projects” and their views on the process. The study was conducted with the participation of 67 prospective science teachers. Project proposal forms and reflective reports were used in the study, which was conducted in the pedagogical activity research method- in collecting the data. The data coming from the reflective reports were then put to content analysis. It was remarkable in consequence that the majority of the prospective teachers ’levels of designing projects were inadequate. The prospective science teachers stated that they had learned the stages of scientific projects in the process of project designing and that they also became skillful at collaborating, researching, problem-solving, writing in academic language, working in a planned manner and at communicating